Management of perianesthesia in benign prostate hyperplasia patients with transvesica prostatectomy and uncontrolled hypertension: A case report - Suandika Made; Puspita Valentina Intan Ayu; Utami Tin (BIO Web of Conferences)
The prevalence of Benign Prostate Hyperplasia (BPH) increases at the age of 40 years to 90 years. Anaesthesia in elderly patients with comorbidities can be difficult for anaesthesiologist. The minimum dose option is used to minimize the occurrence of myocardial depression and other complications. In this paper, we describe the management of anaesthesia for Transvesica Prostatectomy (TVP) surgery for elderly patients with BPH accompanied by uncontrolled hypertension. The method used in this research is a case study with data collection techniques through observation, interviews, and looking at the results of examining related data. The research subjeck was a male patient with a diagnosis BPH who underwent TVP. The result and conclusion of this study refer to the collaborative use of Subarachnoid Block (SAB) or spinal anesthesia induction drugs (Bupivacaine and Fentanyl) with consideration of the minimum dose due to patient’s advanced age and minimizing the occurrence of morbidity and mortality. The intervention given regarding anesthesia health problems which was carried out by providing anesthesia nursing care during the perioperative phase showed good results and without complications that disrupted the patient’s future life